ШАЙЫР-ЖЫРАЎЛАР ДӨРЕТИЎШИЛИГИ ҲӘМ КӨРКЕМЛИК ИЗЛЕНИСЛЕР - Торткулбаева, Т. (SCIENCE and SOCIETY, 2020)
The article deals with peculiaritics of literary works of kazakh poets and bards of XV-XIX centuries, their literary heritages and rich themes, genre and literary- aethetic characters. Futher more author presents different scolars hypothesis on the literary texts.